PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN MEMILIH PADA MAHASISWA SEKOLAH TINGGI ILMU MANAJEMEN INDONESIA (STIMI) - MEULABOH - Chiariyaton Chairiyaton; Nani Verawati (universitas teuku umar, 2019)
The objective of this research was to analyze the influence of marketing mix strategy consisted of product, price, location, people, process, and tangibles on decision to choose at STIMI, Meulaboh.The research used descriptive statistical method with descriptive explanatory approach. The data were gathered by conducting interviews, questionnaires, and documentary study. The population was all students of STIMI, Meulaboh, in the academic year of 2013, and 106 of them were used as the samples. Measuring scale used interval scale and analyzed by using multiple linear regresstion. The result of equation showed that, simultaneously, the variables of product, price, location, people, process, and tangibles could influence decision to choose STIMI, Meulaboh. Partially, product had positive and direct influence on decision to choose at STIMI, Meulaboh. price had positive and direct influence on decision to choose, location had positive and direct influence on decision to choose, people had positive and direct influence on decision to choose, process had positive and direct influence on decision to choose, and tangibles had positive and direct influence on decision to choose at STIMI, Meulaboh.